Mentoria como processo de educação não formal - Oliveira Filho, Benício José de (2023)
The objective of this work was to understand the impacts of mentoring on the lives of those who sought their sessions. Mentoring is not far from other audiences, but in particular we seek to understand how entrepreneurs have pursued their search and what developments they have noticed after and during the sessions. Mentorship is characterized by its relationship between mentor (more experienced person, who stimulates, guides and even serves as a model and inspiration) and mentee (person with less experience and desire for more practical knowledge). In this way, we started this work, understanding the origins and consequences of non-formal education. Since the emergence of the term in the 60s and 70s of the last century until its broader understanding today, it was possible to understand that not only within the school institution does knowledge exist or is generated. The very forces that act on society bring to light new demands and needs for access to knowledge. Understanding non-formal education, we will advance on the vision of Carls Rogers and his new approach to education. Leaving it to be an asset only of the educational institution, Rogers presents in his works context and basis for us to start understanding about new possibilities of understanding education. For Rogers, it necessarily needs to start from the demands of those who request them. What will be possible to perceive is that within the Rogerian vision, an education must be born from the needs of the being and no longer from the imperative that is often imposed by institutions. In view of these two important recent developments in the educational universe, it was our objective to understand whether mentoring could both be a possibility of non-formal education, as advocated by Rogers, would it be centered on the human person. For this, we searched through fifteen interviews with entrepreneurs who resorted to mentoring sessions in the most diverse formats in recent years to understand what were the impacts on their lives of the sessions. Applying the framework analysis technique to the interviews, we advanced through all the stages of the process, culminating in a conclusion that presents important results for us that cannot be disregarded when the theme is non-formal education. Mentoring advances as a possibility of accessing knowledge by uniting mentor and mentee and generating real impacts in the lives of those who use this method. Reading this work presents important data and dimensions of mentoring in Brazil.(AU)